Is there a nascent plate boundary in the Northern Indian Ocean? - Coudurier‐Curveur, Aurélie (2020)
The northern Indian Ocean has been widely recognized as an area of broadly distributed deformation within the composite India‐Australia‐Capricorn plate, hosting several diffuse boundary zones and a diffuse triple junction. The occurrence, along reactivated fracture zones, of the exceptionally large (Mw = 8.6 and Mw = 8.2) 2012 Wharton Basin strike‐slip earthquakes, however, questions whether this composite plate is breaking apart along a discrete boundary. Using recent bathymetric and seismic data, we analyze the most prominent fracture zone (F6a), whose structural trace is particularly well expressed. We identify 60 kilometric‐scale pull‐apart basins with geometric properties (length/width ratios) similar to those observed along continental strike‐slip plate boundaries. Four of the pull‐aparts formed above narrow, subvertical faults extending into the oceanic crust. Within the broad Wharton deformation zone, the significant slip rates (0.8 to 2.5 mm/yr) and unusually large coseismic displacements recorded along F6a suggest that it may be a nascent plate boundary.